(untitled) (Archive of Conferences, 2021)
The application of modern information and communication technologies (ICT) to the identification of biological organisms (objects) is difficult. According to world experience, there are several ways to identify biological objects: morphological features, sample cells, chemical composition, DNA, etc. The largest world of biological objects is the animal world. In order to identify all their types in our country, it is necessary to collect a large number of collections, digitize and analyze information about them.